Update on pulse corticosteroid therapy for the management of alopecia areata - Jolina Bernhardt; Joerg Wenzel (Wiley, 2024)
Abstract Alopecia areata is a nonlife‐threatening autoimmune disorder and often requires systemic treatment to stop the disease from progressing. Pulse corticosteroid therapy (PCT) is a common way to treat severe alopecia areata although the exact benefit on this treatment remains unclear. The aim of this article is to update current knowledge of hair regrowth rates after PCT. Twenty studies with a total of 2144 patients were reviewed. Eight out of 20 studies allow statements on patients who did not respond at all on PCT. From 680 patients in those eight studies, 211 showed no response, which equals a rate of 31.02%. However, nine out of the 20 studies point out how many patients achieved hair regrowth >50% or a reduction in Severity of Alopecia Areata Tool Score by >50%: 131 patients out of 272 achieved a response with >50% hair regrowth, which corresponds to a rate of 48.16%. Complete regrowth of hair was observed and documented in nine studies: Out of the 1757 patients, 677 showed full regrowth leading to a complete response rate of 38.53%. At University Hospital Bonn, Department of Dermatology, Germany, PCT has been an established treatment for severe alopecia areata over the past decades. Nevertheless, many unwanted side effects were observed. A retrospective study on hair regrowth after PCT was performed in 2022 and is also part of this article. Nineteen studies from literature search through the PubMed database and the one own study led to a total of 20 studies being reviewed in this article.